Study and development of the technology for hardening rope blocks by reeling - Dykha, Aleksandr; Marchenko, Dmytro; Artyukh, Vitaliy; Zubiekhina-Khaiiat, Oleksandra; Kurepin, Viacheslav (Eastern-European Journal of Enterprise Technologies, 2018)
The study of the efficiency of hardening the parts working in spalling conditions through reeling with rollers were performed with the help of physical simulation and showed the high effect of hardening cast steels (a 10- to 14-fold increase in durability). The depth and degree of work hardening during plastic deformation of the surface layer were studied by the method of regression analysis. It was found that the 95-% confidence intervals for the depth of work hardening calculated from the results of measurements of yield strength make up 11‒36 % of the hardening depth and 32‒75 % by the hardness measurements. Electrography examination has shown that an increase in the degree of work hardening when reeling with a needle roller manifests itself in a higher dislocation density and cell size decrease in the substructure of ferrite grains. Diffusion of chemical elements in the surface layer in the process of surface deformation was studied with an analysis of the change of the surface microhardness. It was established that the content of Cr and C decreased by 20‒30 % in the transition zone and increased to 10‒15 % in the hardened layer. The main mechanism of diffusion during SFW is the dislocation density gradient. The process of the contact friction surface wear during reeling with consideration of slippage was investigated. It was proved that roughness of the friction surfaces affects the coefficient of friction and the rate of tribo-contact wear during reeling with slippage. For example, with a decrease in surface roughness after reeling with rollers, coefficient of friction for the lubricated surfaces decreases. A procedure for determining conditions of reeling with a wedge roller was developed. A method, technology, and a device for reeling the rope blocks with a wedge roller were developed to provide low roughness and high degree of work hardening of the surface. Optimal reeling conditions were found due to experiment planning using the steep convergence method. The obtained results of calculations will serve as initial data in designing working elements of the reeling devices and developing technological processes for strengthening parts. The conducted studies will find their future use in evaluation of the wear processes taking into account slippage of the «rope block – rope» friction couple.